PENINGKATAN KETERAMPILAN MENULIS PUISI MENGGUNAKAN MODEL PICTURE AND PICTURE SEKOLAH DASAR - Yulita, Yulita; Kresnadi, Hery; Kaswari, Kaswari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractPoetry writing skills are skills to express feelings and thoughts in writing. The general problem in this study is whether the picture and picture learning model can improve poetry writing skills in class III of School Elementary School 05 Nyandung Kabupaten Bengkayang. This study aims to improve poetry writing skills using the picture and picture learning model. This research uses descriptive method, form of action research class (PTK) and is collaborative. Subjects in this study were researchers as teachers and students of class III which amounted to 35 students. This research was conducted in even semester. The procedures used are planning, implementation, observation and reflection. Techniques used are observation and scrutiny of documents, data collection tool is an observation sheet and document scrutiny sheet. Data analysis was conducted between researcher and observer collaboration. The results of the study of poetry writing skills using picture and picture learning model in the first cycle an average score of 51.1. In cycle II the average score 64.49.In cycle III get an average value of 74. It can be concluded that using the picture and picture learning model can improve the writing skills of third grade students of State Elementary School 05 Nyandung Kabupaten Bengkayang. Keywords: Writing Skills, Picture and Picture